Goals, struggles, and coping strategies of Koreans in Iloilo City. - Galanza, Ivy Rose
This is a phenomenological study which sought to describe and detrmine the following: 1) the goals of Koreans in coming to Iloilo City; 2) the problems and sources of stress expreienced by Koreans in Iloilo City; and 3) their coping strategies in dealing with these problems and sources of stress. The subjects were purposely chosen: three females and seven males., Interview schedules were used to determine the variables under investigation. The results showed that ghoals of Koreans in coming to Iloilo City are to learn English, finish high school and colleg education, raise their family and invest in business. The problems that they encounter revovle around culture, language, school, personal, transportation, facilitie, physical environment, government policies, and others. The coping strategies that they employ are emotion-focused and problem-focused coping.